Technical education, non-cognitive skills and labor market outcomes: Experimental evidence from Brazil - Juliana Camargo; Lycia Lima; Flavio Riva; André Portela Souza (IZA Journal of Labor Economics, 2021)
This paper describes the results from an evaluation of a public policy that offers scholarships to current and former public high school students, so that they can attend technical and vocational education courses free of charge. We use a waiting list randomized controlled trial in four municipalities in a southern Brazilian State (Santa Catarina) to quantify the effects of the program on school progression, labor market outcomes and non-cognitive skills. Our intention-to-treat estimates reveal substantial gender heterogeneity two years after program completion. Women experienced large gains in labor market outcomes and non-cognitive skills. Employment rose by 21 percentage points (or approximately 33%) and the gains in earnings are of more than 50%. Also, women who received the offer scored 0.5σ higher on the synthetic index of non-cognitive skills and 0.69σ higher on an extraversion indicator. We find no effects on the male sub-sample. These findings corroborate the evidence on gender heterogeneity in the labor market effects of technical and vocational education programs. We also perform a series of exercises to explore potential channels through which these effects arise.
Keywords: C21; I38; J24; 330; Vocational Education; Human Capital; Non-cognitive Skills; Labor Market Outcomes